Co(II)-Catalyzed Desilylative Annulation of Benzamides and Acrylamides with Alkynylsilanes: Access to 3-Methyleneisoindolin-1-one and 5-Methylene-1H-pyrrol-2(5H)-one Derivatives - Wang, Jingyu; Teng, Qiuxun; Lin, Cong; Gao, Fei; Liu, Xiuhong; Shen, Liang (Synthesis, 2020)
The cobalt-catalyzed desilylative annulation of C(sp2)–H bonds of benzamides and acrylamides with alkynylsilanes assisted by an 8-aminoquinolyl directing group is reported. A variety of benzamides and acrylamides were compatible in this protocol to construct various 3-methyleneisoindolin-1-one and 5-methylene-1H-pyrrol-2(5H)-one derivatives with Z-configuration selectivity in moderate to high yields.
Keywords: cobalt catalysis; desilylative annulation; benzamides and acrylamides; alkynylsilanes; 3-methyleneisoindolin-1-one; 5-methylene-1H-pyrrol-2(5H)-one